Linkage between Knowledge Sharing, Organizational Culture, Employee Creativity in Manufacturing Organizations - Md Fauzi Ahmad; Naima Andleeb; Mohd Fahrul Hassan; Nor Aida Abdul Rahman; Arman Shah Abdullah; Mohd Nasrun Mohd Nawi (International Journal of Supply Chain Management, 2020)
Creativity relevant literature relevant is diverse in approaches. As a result, there has been a lack of cohesive theoretical understanding of how employee creativity operates and gets affected in organizations. The purpose of this paper is to develop a conceptual framework of employee creativity (EC) along with knowledge sharing (KS), organizational culture (OC), Motivation and towards employee creativity in manufacturing industry. The literature review demonstrates the importance of employee creativity in manufacturing industry. Ever increasing competitive environment requires more competent and creative workforce in manufacturing organizations. Critical issues in designing this framework is to facilitating the factors that contribute in employee creativity in manufacturing industries. The direction of current framework has been found from past literature. Anticipated outcomes from KS and OC in manufacturing industry include application of motivation as a mediator. A further empirical study will be carried out to examine the effect of the proposed framework and hypotheses. This paper provides a comprehensive framework that contributes the empirical evidence to the academicians, act as a platform to the manufacturing industry.